2016
DOI: 10.3389/fmicb.2016.01389
|View full text |Cite|
|
Sign up to set email alerts
|

Orf Virus 002 Protein Targets Ovine Protein S100A4 and Inhibits NF-κB Signaling

Abstract: Orf virus (ORFV), a member of Parapoxvirus, has evolved various strategies to modulate the immune responses of host cells. The ORFV-encoded protein ORFV002, a regulator factor, has been found to inhibit the acetylation of NF-κB-p65 by blocking phosphorylation of NF-κB-p65 at Ser276 and also to disrupt the binding of NF-κB-p65 and p300. To explore the mechanism by which ORFV002 regulates NF-κB signaling, the understanding of ORFV002 potential binding partners in host cells is critical. In this study, ovine S100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The regulation of NF-κB includes the regulation of IκB in the cytoplasm, and posttranslational phosphorylation, acetylation, and methylation in the nucleus. The ORFV 002, 024, 073, 119, and 121 genes have been reported that play roles in NF-κB pathway regulation [32][33][34][35][36][37][38].…”
Section: Orfv and Immune Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of NF-κB includes the regulation of IκB in the cytoplasm, and posttranslational phosphorylation, acetylation, and methylation in the nucleus. The ORFV 002, 024, 073, 119, and 121 genes have been reported that play roles in NF-κB pathway regulation [32][33][34][35][36][37][38].…”
Section: Orfv and Immune Evasionmentioning
confidence: 99%
“…ORFV002-encoded protein can inhibit the activation of NF-κB pathway induced by TNF-α and ORFV virus infection, which may through interfering the interaction between NF-κB-p65 and P300 in the nucleus block the acetylation of NF-κB-p65 Lys310 when phosphorylation occurs at ORFV002 Ser 276 [32,33]. The 52 amino acids of ORFV002 N terminal may interact with protein S100A4 [34].…”
Section: Orfv and Immune Evasionmentioning
confidence: 99%
“…ORFV genes have been reported to play roles in NF-κB pathway regulation. [62][63][64][65][66][67][68] The ORFV002 gene, located in the nucleus, encodes a protein inhibiting activation of the NF-κB pathway by TNF-α and ORFV infection. ORFV002 may interfere with the interaction between NF-κB-p65 and P300 in the nucleus, thereby blocking the acetylation of NF-κB-p65 Lys310 when ORFV002 Ser276 is phosphorylated.…”
Section: Orfv and Immune Escapementioning
confidence: 99%
“…62,63 Additional studies have shown that ORFV002 inhibits NF-κB activation through interacting with the S100 calcium binding protein A4 (S100A4). 64 Recent studies have found that the ORFV024 protein blocks the NF-κB signaling pathway by combining with LAGE3 to inhibit the phosphorylation of inhibitor of nuclear factor kappa-B kinase (IKK) complex. ORFV024 affects the phosphorylation of NF-κB-p65, inhibiting the secretion of important cytokines and regulating the host immune response, 65 suggesting that ORFV024 is a virulence determinant for ORFV in the natural host.…”
Section: Orfv and Immune Escapementioning
confidence: 99%
“…Initially, primary lamb testis and primary lamb kidney cells were commonly used for ORFV isolation [6]. Primary fetal lamb muscle cells [7], ovine fetal turbinate cells [8], and goat skin fibroblast cells [9] have also been widely used for ORFV isolation. Madin-Darby bovine and Madin-Darby ovine kidney are the most commonly used cell lines for ORFV isolation and propagation [10].…”
Section: Introductionmentioning
confidence: 99%